Studi Respon Imun Humoral Mencit, Tikus, dan Ayam terhadap Infeksi Toxoplasma Gondii - Gifti Rosalina Ratnaningrum; Dana Meida; Andhini Mutiara Putri; Hilda Syara Shita Devi; Dwi Priyowidodo (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2016)
Toxoplasmosis is a disease caused by the protozoan Toxoplasma gondii. T. gondii is an obligate intracellular parasite that is transmitted by congenital and acquisition. T. gondii can infect all warm-blooded animals and are zoonotic. It is estimated that more than a third of the world’s population is infected by T. gondii. Chicken is one of the animals that can be infected with T. gondii and plays an important role in the spread of this disease to humans because it is one of the animals used as a source of animal feed. Mice and rats are also play an important role in the spread of toxoplasmosis in the definitive host, especially in cats. T. gondii infection is usually asymptomatic, but in certain circumstances, such as when the host’s immune system is weakened, this parasite can causeserious illness. This study were aimed to determine the humoral immune response against T. gondii infection in mice, rats and chickens by serological Latex Agglutination Test (LAT) using Pastorex-Toxo® kit. Two weeks oldbroiler chickens were 8 heads, Wistar strain rats aged 8 weeks as many as 18 heads and strain Balb C mice aged 8 weeks as many as 13 cows used in this study. Animals were grouped into two groups, namely the control andinfection groups. Mice, rats, and chickens were infected each with 103, 107 and 105 takizoit by intra-peritoneal injection. Blood samples were taken from the animals and infection control from day to-1, 2, 3, 4, 5, 6 for mice,the to-1, 2, 3, 4, 5, 6, 7, 8 for rats, and day - 2, 4, 14 for chicken by intracardia 3 ml, then put in a non-EDTA tubes and centrifuged at a speed of 10,000 rpm for 5 minutes to collect serum. The results showed a humoral immuneresponse against T. gondii in rats began to appear on day 5 post-infection, chickens began to emerge the 2nd day post infection, whereas mice do not indicate a humoral immune response against T. gondii post infection.